PERLINDUNGAN HUKUM HAK ATAS TANAH MASYARAKAT DESA GALUGA BOGOR AKIBAT PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Martinus Siki (JURNAL ILMIAH LIVING LAW, 2015)
The study refered to the case of garbage landslide of TPAS Galuga Bogor on 2010, which gave impact to the removal of the object of communal land, in order to analyze whether the compensation also the handling of that impact were not carried out in accordance with the regulation. By the approach of empirical and normative jurudical analytical methods, this study prior to the land acquisition for constructing the TPAS Galuga Bogor, which brought inappropriate waste management in accordance with the provision of the legislation. This caused garbage landslide as well as environmental pollution. In order to avoid the lawsuits, Government of Bogor, as the manager, intentionaly used the pattern of land acquisition for public interest in compensating the object of communal land that was burried by garbage landslide so it would be considered as a case of force majeure. Therefore, it can be concluded that there were deviation and legal violation of land acquistion, waste management, and the handling of the impact of TPAS Galuga Bogor so that communities and NGOs can prosecute class action lawsuits to the municipal government of Bogor, who should be responsible for any loss due to the impact of insufficient management of TPAS Galuga Bogor.